How can developing countries harness biotechnology to improve health? - Persad Deepa L; Berndtson Kathryn; Daar Abdallah S; Singer Peter A (BMC, 2007)
Abstract Background The benefits of genomics and biotechnology are concentrated primarily in the industrialized world, while their potential to combat neglected diseases in the developing world has been largely untapped. Without building developing world biotechnology capacity to address local health needs, this disparity will only intensify. To assess the potential of genomics to address health needs in the developing world, the McLaughlin-Rotman Centre for Global Health, along with local partners, organized five courses on Genomics and Public Health Policy in the developing world. The overall objective of the courses was to collectively explore how to best harness genomics to improve health in each region. This article presents and analyzes the recommendations from all five courses. Discussion In this paper we analyze recommendations from 232 developing world experts from 58 countries who sought to answer how best to harness biotechnology to improve health in their regions. We divide their recommendations into four categories: science; finance; ethics, society and culture; and politics. Summary The Courses' recommendations can be summarized across the four categories listed above: Science - Collaborate through national, regional, and international networks - Survey and build capacity based on proven models through education, training, and needs assessments Finance - Develop regulatory and intellectual property frameworks for commercialization of biotechnology - Enhance funding and affordability of biotechnology - Improve the academic-industry interface and the role of small and medium enterprise Ethics, Society, Culture - Develop public engagement strategies to inform and educate the public about developments in genomics and biotechnology - Develop capacity to address ethical, social and cultural issues - Improve accessibility and equity Politics - Strengthen understanding, leadership and support at the political level for biotechnology - Develop policies outlining national biotechnology strategy These recommendations provide guidance for all those interested in supporting science, technology, and innovation to improve health in the developing world. Applying these recommendations broadly across sectors and regions will empower developing countries themselves to harness the benefits of biotechnology and genomics for billions who have long been excluded.